The Effect of Financial Goals and Financial Knowledge on Personal Financial Sustainability and Retirement Saving Behavior: ผลกระทบของการตั้งเป้าหมายทางการเงิน และการให้ความรู้ทางการเงิน ต่อความยั่งยืนทางการเงินส่วนบุคคลและพฤติกรรมการออมเพื่อวัยเกษียณ - Chaiphat, Channarong; Tangtammaruk, Peera (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ กำลังแรงงานของประเทศไทยเกือบร้อยละ 50 กำลังเคลื่อนเข้าสู่วัยเกษียณในอีก 10-20 ปีข้างหน้า ขณะที่ค่าใช้จ่ายในการดูแลสุขภาพเพิ่มขึ้นอย่างต่อเนื่องจากกลุ่มโรค NCDs ที่เป็นโรคไม่ติดต่อเรื้อรัง นอกจากนี้ผลการศึกษาจากงานวิจัยในอดีตระบุว่าคนไทยยังมีความรู้ทางการเงินเพื่อเตรียมพร้อมการเกษียณไม่เพียงพอ ดังนั้น ความสุขทางการเงิน จึงเป็นเป้าหมายสำคัญในการใช้ชีวิตหลังเกษียณการทำงาน งานวิจัยนี้จึงตั้งใจ จะศึกษาปัจจัยที่มีผลต่อความยั่งยืนทางการเงินในระดับบุคคล และทำการวิจัยเชิงทดลองเพื่อวิเคราะห์ผล ของการสะกิดที่มีต่อพฤติกรรมการออมการลงทุนเพื่อวัยเกษียณกับกลุ่มตัวอย่างที่เป็นพนักงานมหาวิทยาลัย ผลการศึกษาพบว่า กลุ่มตัวอย่างที่สุขภาพการเงินดีมีร้อยละ 43.02 สุขภาพการเงินเสี่ยงมีร้อยละ 23.26 และสุขภาพการเงินวิกฤตมีร้อยละ 33.72 ส่วนปัจจัยด้านประชากร ด้านทักษะทางการเงิน และด้านการวางแผนการเงิน ล้วนเป็นปัจจัยที่มีผลต่อความอยู่รอดทางการเงิน สำหรับผลการศึกษาเชิงทดลอง พบว่า การกำหนดนโยบายให้ตั้งเป้าหมายทางการเงิน และการสะกิด (Nudge) โดยการชี้นำ (Priming) ความรู้ทางการเงิน ส่งผลให้กลุ่มทดลองมีแนวโน้มที่จะอยู่รอดทางการเงินในวัยเกษียณมากกว่า เมื่อเปรียบเทียบกับการไม่แทรกแซงใดๆ ประมาณร้อยละ 20 อย่างไรก็ตามการชี้นำด้วยข้อมูลทางการเงินที่สำคัญๆ เป็นวิธีการที่เหมาะสมกว่า เพราะทำให้คนปรับพฤติกรรมการออมการลงทุนของตนเองโดยสมัครใจ และยังสามารถแก้ปัญหาอคติเชิงพฤติกรรม 3 ข้อ ที่ทำให้คนไม่ออมเงิน คือ ความเฉื่อย ความกลัวการสูญเสีย และความลำเอียงในปัจจุบัน ดังนั้นการสะกิดโดย วิธีชี้นำข้อมูลที่สำคัญๆ ตามหลักของเศรษฐศาสตร์พฤติกรรมเป็นอีกทางเลือกหนึ่งที่หน่วยงานทั้งภาครัฐและเอกชนสามารถนำมาประยุกต์ใช้เพื่อเตรียมคนเข้าสู่วัยเกษียณที่มีความสุขทางการเงิน และลดภาระของรัฐบาล ในการดูแลผู้สูงอายุ ABSTRACT In the next 10 to 20 years, almost 50 percent of Thai laborers will move into retirement age, alongside with an increasing trend of healthcare costs from non-communicable diseases (NCDs). Additionally, recent studies indicate that Thai people still do not have enough financial knowledge for retirement. Therefore, financial well-being is a crucial goal of life after retirement. This paper aims to examine the factors affecting personal financial sustainability, as well as apply the experimental economic approach to study the effects of (1) financial targeting policy and (2) priming as a “nudge” on retirement savings behavior using university staff as a case study. This paper found that 43.02%, 23.26%, and 33.72% of the samples were in good, risk, and critical financial health status, respectively. In addition, some of the demographic factors, financial skills, and financial planning were seen to be factors that significantly affect the financial survival ratio. On the other hand, the experimental results show that setting financial targets as a policy, and priming some important financial knowledge, also increase the probability of having financial well-being at around 0.2 (20%) when compared to the control group. Finally, we suggest that priming using the behavioral economic nudge theory can be considered as another retirement planning option for both government and private organizations in order to prepare for an era of an aging society. This will not only effectively reduce the causes of not saving from inertia, avoidance of loss, and bias in the present, but will also help adjust people’s savings behavior without being forced.